2012
DOI: 10.1039/c1ee02668b
|View full text |Cite
|
Sign up to set email alerts
|

Advances in high permeability polymeric membrane materials for CO2separations

Abstract: Advances in high permeability polymeric membrane materials for CO2 separations Du, Naiying; Park, Ho Bum; Dal-Cin, Mauro M.; Guiver, Michael D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
312
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(316 citation statements)
references
References 120 publications
(195 reference statements)
4
312
0
Order By: Relevance
“…We varied the concentration of O 2 in the ultraviolet irradiation atmosphere at a fixed exposure time (20 min) and found significant differences in pure gas permeation properties of PIM-1 membrane and ultraviolet/ozone-modified PIM-1, as shown in Fig. 3b-c. Pristine PIM-1 membrane presents a CO 2 permeability of B4,500 Barrer, a CO 2 /N 2 selectivity of B20 and a CO 2 /CH 4 selectivity at B13, which are in agreement with the literature data 46 . Control experiments of ultraviolet exposure in pure N 2 showed no discernible difference in properties to that of pristine polymer.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We varied the concentration of O 2 in the ultraviolet irradiation atmosphere at a fixed exposure time (20 min) and found significant differences in pure gas permeation properties of PIM-1 membrane and ultraviolet/ozone-modified PIM-1, as shown in Fig. 3b-c. Pristine PIM-1 membrane presents a CO 2 permeability of B4,500 Barrer, a CO 2 /N 2 selectivity of B20 and a CO 2 /CH 4 selectivity at B13, which are in agreement with the literature data 46 . Control experiments of ultraviolet exposure in pure N 2 showed no discernible difference in properties to that of pristine polymer.…”
Section: Resultssupporting
confidence: 82%
“…The resulting asymmetric membrane geometry is analogous to TFC membranes. Nevertheless, from a chemical reaction viewpoint, the kinetics of photo-oxidation in PIM-1 could be tuned, that is, by controlling the intensity of ultraviolet irradiation 46 and data reported recently by Bezzu et al 30 and Carta et al 12 The dense membranes (B50 mm) were exposed to ultraviolet irradiation in air for varied time (5-60 min) as marked in the figure, with the membranes sandwiched in quartz glass. The data are measured from pure-gas permeation tests at 4 bar at 22°C.…”
Section: Discussionmentioning
confidence: 99%
“…The most promising materials for membranes to be used in post-combustion gas separation are polymers containing polyethers, namely poly(ethylene glycol) and poly(propylene glycol). [6,35] It was shown that such polymers can provide membranes with properties matching economic requirements of post-combustion separation. Realistic analysis of the separation process indicates that currently it is not possible to reach a CO 2 purity sufficient for transportation and storage in a one stage separation.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane technology can provide energyefficient, cost-effective separations for a wide range of industries [27,33,[104][105][106][107]. For membrane separations, there is a balance between the separation that is achievable (i.e., selectivity) and the productivity (i.e., flux or permeance).…”
Section: Membranesmentioning
confidence: 99%